Baudelaire’s Aesthetic - Del Nevo, Matthew (Sophia, 2010)
This paper will take up the work of Charles Baudelaire, poetic and critical, in order to present the Baudelairean aesthetic and to make a case for its relevance in our judgments about art today. Baudelaire was the first poet of the modern built environment and is known as the father of modern poetry. While his poetry is still admired, his aesthetic has been historicised: deemed to belong to that time and place in which Baudelaire wrote. This paper will argue that this historicisation by subsequent aesthetic theory and philosophy is a suppression of something integral to art and artists, without which art is liable to lose what is true about it and sink into a morass of irrelevance and triviality, or (as will be argued has partly happened) may become devoid of any value beyond the business interests that control it. In this regard, it will be suggested, Baudelaire’s aesthetic has important redeeming qualities.